2020
DOI: 10.1016/j.autneu.2019.102600
|View full text |Cite
|
Sign up to set email alerts
|

Bladder overactivity and post-void residual: Which relates more to systemic atherosclerotic markers?

Abstract: Several studies have shown relationship between the lower urinary tract dysfunction (LUTD) and atherosclerosis. However, no study is available to see which LUTD relates more to atherosclerosis, among detrusor overactivity and post-void residual. In order to answer this question, we present data of urodynamic and atherosclerosis tests. Methods: We performed standard urodynamics and two atherosclerosis tests, i.e., a cardio-ankle vascular stiffness index (CAVI) test and a duplex carotid ultrasonography. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The test methods for determining LUTD (using equipment from Urovision and Life-Tech Inc., Houston, TX, USA) were according to the International Continence Society standards. They included ultrasound echography of the prostate gland in all men (men with a prostate volume > 20 mL were excluded), a nerve conduction study (Neuropack M2; Nihon Kohden Inc., Tokyo, Japan), a cardio-ankle vascular stiffness index test [6] (pulse wave velocity-derived parameter) using a VaSera instrument (Fukuda Denshi Inc., Tokyo, Japan), and an ultrasound Doppler echography (SSA-260A; Toshiba, Inc, Tokyo, Japan). Data were analyzed by Student’s t test and Mann-Whitney U test.…”
Section: Methodsmentioning
confidence: 99%
“…The test methods for determining LUTD (using equipment from Urovision and Life-Tech Inc., Houston, TX, USA) were according to the International Continence Society standards. They included ultrasound echography of the prostate gland in all men (men with a prostate volume > 20 mL were excluded), a nerve conduction study (Neuropack M2; Nihon Kohden Inc., Tokyo, Japan), a cardio-ankle vascular stiffness index test [6] (pulse wave velocity-derived parameter) using a VaSera instrument (Fukuda Denshi Inc., Tokyo, Japan), and an ultrasound Doppler echography (SSA-260A; Toshiba, Inc, Tokyo, Japan). Data were analyzed by Student’s t test and Mann-Whitney U test.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there was no significant difference in vascular function between the patients with a large post-void residual volume and the control The authors suggested that a large post-void residual volume might be associated with local factors, and the autonomic dysfunction of the bladder might be related to systemic vascular pathologies. 38 Increased arterial stiffness may affect tissue healing by causing vascular dysfunction. Koguchi et al cross-sectionally examined OAB symptoms in patients who underwent robot-assisted laparoscopic radical prostatectomy for prostate cancer.…”
Section: Cardio Ankle-vascular Index In Overactive Bladdermentioning
confidence: 99%
“…2 Furthermore, LUTS should be recognized and treated as early as possible. Although symptoms manifest in the context of LUT, LUTS can be a sign of serious medical conditions with an etiology in other organic systems, [3][4][5][6][7][8][9][10] or it can serve as base for the development of other diseases, [11][12][13][14] and it significantly decreases the quality of life. [15][16][17][18] However, primary health care, and especially patients, still do not recognize LUTS early enough.…”
Section: Introductionmentioning
confidence: 99%